ANALYSIS OF THE IMPACT OF EMOTIONAL INTELLIGENCE ON ORGANISATIONAL PERFORMANCE: A BANKING PERSPECTIVE - Danquah, Emelia (British Journal of Marketing Studies, 2014)
The popularity of emotional intelligence in service marketing is on the ascendency. Its popularity could also be attributed to its potential for business growth. This study seeks to analyse and verify the impact of emotional intelligence on organisational growth in the banking sector of Ghana. The study adopts a quantitative research technique in which hypotheses are tested to verify the relationship between emotional intelligence and organisational growth in terms of return on investment. The study is based on 20 banks in Ghana. Pearson’s correlation test, partial correlation test and ordinary least squares regression analysis were used in testing hypotheses. Findings of this study indicate that emotional intelligence is positively related to organisational performance (p < .05). Emotional intelligence also significantly predicts organisational performance (p < .05) with a variability of 30.6%, while it has a significant moderating effect on the relationship between customer satisfaction and business performance (p < .05). It is recommended that banks formalise and regularise their investments in the acquisition of emotional intelligence skills for maximum organisational performance.